Synergistic high-performance electromagnetic and microwave absorption of BaFe12O19/NiFe2O4/carbon nanotube/graphene oxide nanocomposites - Elmahaishi, Madiha Fathi; Azis, Raba’ah Syahidah; Ismail, Ismayadi; Katibi, Kamil Kayode; Matori, Khamirul Amin; Muhammad, Farah Diana; Saat, Nor Kamilah; Kechik, Mohd Mustafa Awang; Pah, Lim Kean; Kien, Chen Soo; Ibrahim, Norazila (Springer, 2025)
This study focuses on a sustainable route for fabricating high-performance microwave absorbers using green precursors and a hybrid nanocomposite. Multiwalled carbon nanotubes (MWCNTs) were in situ grown from waste cooking oil (WCO) using a modified thermal vapor deposition method, while iron oxide (Fe₂O₃) recovered from waste steel (WS) served as the mechanochemical precursor for synthesizing hard barium hexaferrite (BaFe₁₂O₁₉) and soft nickel ferrite (NiFe₂O₄). These ferrite nanoparticles were then integrated with the as-grown MWCNTs and graphene oxide (GO), yielding two ternary systems of BaFe₁₂O₁₉/NiFe₂O₄/MWCNTs (BaF/NiF/CNTs) and BaFe₁₂O₁₉/NiFe₂O₄/MWCNTs/GO (BaF/NiF/CNTs/GO). A thorough characterization, including X-ray diffraction, Raman spectroscopy, Field Emission Scanning Electron Microscope (FESEM), and Vibrating Sample Magnetometer (VSM), confirmed phase purity, nanoscale dispersion, and exchange-coupled magnetic behavior. Electromagnetic parameters (ε′, ε″, μ′, μ″) were measured over 8–18 GHz (X-Ku bands) using a vector network analyzer. Compositing barium ferrite (BaFe)/nickel ferrite (NiFe) as a magnetic phase with MWCNT/GO as a dielectric phase improved the electromagnetic absorption properties. Remarkably, the BaFe/NiFe/CNTs/GO composite achieved a minimum reflection loss of −47.75 dB at 13.59 GHz and an effective absorption bandwidth of 4.64 GHz (RL ≤ −10 dB) at a 2.0 mm thickness. Thus, the facile, waste-derived synthesis and the superior microwave absorption performance of BaFe/NiFe/CNTs/GO nanocomposite demonstrate its promising potential for high-frequency applications.